A study of learning leadership of child care teacher under the local government organization Sisaket Province - Prasarnthong, Pornta; Wongwatkasem, Wiralphat; Suwattanapong (Journal for Developing the Social and Community, 2022)
This research have a purpose to study and compare the level of opinions on learning leadership of child care teacher under the local government organization Sisaket Province by gender, position and work experience. The population used in the research was 648 people. Research in instrument as a questionnaire, it was characterized as a 5-level estimation scale with a reliability of 0.81. Data analysis to analiyzed by frequency, percentage, mean, standard deviation, t-test, F-test , Scheffe's method. The results of the research were as follows: 1. A study of learning leadership of teachers who took care of children under local administrative organizations in Sisaket Province. It was found that the overall opinions were at a high level. When considering each aspect, it was found that Learning leadership of teachers who care for children at a high level in all aspects The averages were arranged in descending order, i.e. the development of the learning process. Development of innovative media and educational technology course development development of learning resources Providing supervision within educational institutions. 2. The opinions of personnel regarding learning leadership education of child care teachers under local administrative organizations in Sisaket Province, classified by gender, were significantly different at 0.05 level, classified by position. Overall and each aspect were significantly different at 0.05 level. classified by work experience. overall is no different.